Implementasi Hot Work Permit System sebagai Upaya Pencegahan Kecelakaan Kerja - Fitri Ayu Lestari; Andiko Nugraha Kusuma; Wiwik Eko Pertiwi (Universitas Faletehan, 2018)
The Hot Work Permit System is a written permission system for doing work that generates a heat source. The aims of this research is to determine the correlation between knowledge, working period, and attitude of workers with the implementation of hot work permit system at the Department of Mechanichal White Paper at PT. Indah Kiat Pulp and Paper Tbk Serang year 2017. The research is cross sectional. The population of this study is all employees at the Department of Mechanichal White Paper which amounted to 50 people. The sample of this study is the total population. Primary data collection using questionnaires with interview techniques. Univariate results showed that 58.0% of workers had high implementation, 66.0% had high knowledge, 74.0% had a working life of ≥ 10 years, and 64.0% had a positive attitude. The result of statistical test shows that there is relation between worker knowledge (Pv: 0,008) and attitude (Pv: 0,000) with hot work permit system implementation. Suggestion to the company to improve the implementation of safety culture about the implementation of hot work permit system, implement training program for welder, and implement socialization system to the workers regarding standard operational procedure (SOP) worker attitude.